Developing physical education benchmark: a preliminary investigation using two standardized test instrument - Ibrahim, Halijah; Mohd. Hashim, Asha Hasnimy; Zainuddin, Zainal Abidin (2006)
The goal of Physical Education Lesson in Malaysia is to assist pupils to become fit through physical activity session and fitness practice. After undergo a period of PE lesson, descriptions on what students should know and, be able to do within a particular movement skills or sport skills is essential to reveal the standard of the program or the curriculum. This study is a preliminary investigation in order to develop the national standard of movement skills achievement in Malaysia Physical Education Curricullum. A study to investigate the expected or required level of movement performance is performed. Two Standardized Test Instrument, McCarron Assessment Neuromascular Development (MAND) and Talent Identification Test (TI) were used to identify fine and gross motor skills of Malaysian young adolescents. Three hundred and thirty students (165 boys, and 165 girls,) age = 13.4, Â±.99 involved in this study. Comparison on five fine motor skill items and five gross motor skills of Malaysian young adolescents with the developed normative data indicated that Malaysian young adolescents scored above average on fine motor skill but scored lower average on gross motor skill as compared to American Population (MAND test). Malaysian young adolescents show below average on the TI test. Results indicated that a culturally appropriate benchmark of Phvsical Education is essential to portray Malaysian movement skills level/ability. In addition by developing the benchmark, the curriculum can always be monitored.